Individual-portal support with a pre-tensioned canopy for a coal mine roadway junction - Rotkegel Marek; Nguyen Phu Minh Vuong; Duong Duc Hai (Studia Geotechnica et Mechanica)
This paper presents an alternative model of individual-portal support structure with a pre-tensioned canopy for coal mine roadway junctions in the geological and mining conditions of underground mines in Vietnam. The aim of the research is to determine the bearing capacity of the individual-portal support structure with various configuration. For this purpose, an analysis of the rock mass behaviour around the three-way roadway junction was carried out using the difference element method-based programme (FLAC3D). Additionally, other analysis of the bearing capacity of the selected individual-portal support structure was also conducted using the finite element method-based programme (COSMOS/M). The geological and mining conditions of Vietnamese mines were taken into account during performing these analyses. Based on the results, the optimal individual-portal support structure was proposed for the roadway junctions driven in the geological and mining conditions of underground mines in Vietnam.